Genomic rearrangements in the aspA-dcuA locus of Propionibacterium freudenreichii are associated with aspartase activity. (September 2022) - Turgay, Meral; Falentin, Hélène; Irmler, Stefan; Fröhlich-Wyder, Marie-Therese; Meola, Marco; Oberhaensli, Simone; Berthoud-dit-Gallon Marchand, Hélène
Abstract: Propionibacterium freudenreichii is crucial in Swiss-type cheese manufacture. Classic propionic acid fermentation yields the nutty flavor and the typical eyes. Co-metabolism of aspartate pronounces the flavor of the cheese; however, it also increases the size of the eyes, which can induce splitting and reduce the cheese quality. Aspartase (EC 4.3.1.1) catalyzes the deamination of aspartate, yielding fumarate and ammonia. The aspartase activity varies considerably among P. freudenreichii strains. Here, the correlation between aspartase activity and the locus of aspartase-encoding genes (aspA ) and dcuA encoding the C4-dicarboxylate transporter was investigated in 46 strains to facilitate strain selection for cheese culture. Low aspartase activity was correlated with a particular genomic rearrangement: low in vitro aspartase activity always occurred in strains with gene clusters aspA - dcuA where the dcuA was frameshifted, producing a stop codon or was disrupted by an ISL3-like element. The low aspartase activity could be due to the protein sequence of the aspartase or a dysfunctional DcuA. The highest values of aspartase activity were detected in strains with aspA1 - aspA2-dcuA with a DcuA sequence sharing 99.07 – 100% identity with the DcuA sequence of strain DSM 20271 T and an additional C4-dicarboxylate transporter belonging to the DcuAB family. Highlights: Strain-dependent ability of P. freudenreichii to utilize aspartate alters cheese quality — important in culture design. P. freudenreichii strains exhibit a diverse gene arrangement around the aspartase-encoding gene. Low aspartase-active P. freudenreichii strains revealed a specific gene arrangement around the aspartase-encoding gene.